UPAYA PENINGKATAN KEMAMPUAN MENGAMATI, MENERAPKAN KONSEP, DAN MEYIMPULKAN PESERTA DIDIK MENGGUNAKAN PEMBELAJARAN BERBASIS PRAKTIKUM - Nurul Khotimah; Lilit Rusyati; Wiwin Sriwulan; Mohammad Ikhsanul Hakim (Program Studi PGSD Universitas Flores, 2023)
The ability to observe, apply concepts, and draw conclusions is an important aspect of science learning. However, there are still students who have low proficiency in these skills. This can hinder their understanding of concepts and their ability to learn scientific knowledge. This research aims to enhance students' abilities in observing, applying concepts, and drawing conclusions in the subject of ecology and biodiversity through practical-based learning in Class VII B of SMP Laboratorium Percontohan UPI. The research conducted is a Classroom Action Research (CAR). The procedural design of this CAR consists of two cycles, each cycle comprising four steps: planning, action implementation, observation, and reflection. The results indicate that practical-based learning effectively improves students' abilities in observing, applying concepts, and drawing conclusions. There was a significant improvement in observation skills from the pre-cycle to Cycle 2, with the average score increasing from 55 to 84. 87% of the students achieved a high category in observation skills. There was also a good improvement in the ability to apply concepts, with the average score increasing from 55 to 77, and 60% of the students achieving a high category. Similarly, there was a significant improvement in the ability to draw conclusions, with the average score increasing from 47 to 72, and 60% of the students achieving a high category. Based on the research findings, it can be concluded that practical-based learning effectively enhances students' abilities in observing, applying concepts, and drawing conclusions.